2011
DOI: 10.5301/hip.2011.8587
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Impaction Grafting in Total Hip Replacement

Abstract: In our series, results were disappointing where a large rim mesh or significant reconstruction was required. In light of these results, our technique has changed in that we now use predominantly larger chips of purely cancellous bone, 8-10 mm3 in size, to fill the cavity and larger diameter cups to better fill the aperture of the reconstructed acetabulum. In addition we now make greater use of i) implants made of a highly porous in-growth surface to constrain allograft chips and ii) bulk allografts combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…We also observed that all loosened cups did not require rerevision because mild groin pain is well tolerated in some patients [12,25]. Although there is a place for IBG, and the advantage of this method is that if a further operation is required, there is likely to be more living bone present; the poorer result when a large rim mesh was used has led surgeons to consider the use of acetabular tantalum augments combined with or without IBG [27]. Metal augments try to create peripheral acetabular containment to facilitate graft impaction [16].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…We also observed that all loosened cups did not require rerevision because mild groin pain is well tolerated in some patients [12,25]. Although there is a place for IBG, and the advantage of this method is that if a further operation is required, there is likely to be more living bone present; the poorer result when a large rim mesh was used has led surgeons to consider the use of acetabular tantalum augments combined with or without IBG [27]. Metal augments try to create peripheral acetabular containment to facilitate graft impaction [16].…”
Section: Discussionmentioning
confidence: 74%
“…Rigby et al [27] and Van Haaren et al [40] also report poor results in patients with these large segmental defects. Rigby et al explain that the mechanism of failure of these cups consisted of movement and rotation of the cup/cement composite within the graft.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The removal of the acetabular component was conducted with the use of purpose-built components such as the Explant Acetabular Cup Removal System (Zimmer, Warsaw, IN, USA). The occurring bone defects were classified according to the Paprosky classification [21]. Furthermore, defects of the dorsal and ventral column were evaluated as these are not included in the Paprosky classification (Table 3).…”
Section: Surgical Therapymentioning
confidence: 99%